2007
DOI: 10.1016/j.mcn.2007.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Rapid, concurrent alterations in pre- and postsynaptic structure induced by naturally-secreted amyloid-β protein

Abstract: In Alzheimer's disease increasing evidence attributes synaptic and cognitive deficits to soluble oligomers of amyloid β protein (Aβ), even prior to the accumulation of amyloid plaques, neurofibrillary tangles, and neuronal cell death. Here we show that within 1-2 hours picomolar concentrations of cell-derived, soluble Aβ induce specific alterations in pre-and postsynaptic morphology and connectivity in cultured hippocampal neurons. Clusters of presynaptic vesicle markers decreased in size and number at glutama… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
99
0
5

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(114 citation statements)
references
References 48 publications
10
99
0
5
Order By: Relevance
“…In fact, the only morphological change found in the hippocampus of A␤-injected rodents displaying memory deficits was the loss of synaptic markers, whereas neither overt neuronal damage nor astrogliosis nor microgliosis were observed, neither 15 nor 2 d after A␤ 1-42 administration. Accordingly, in cultured neurons (in which peripheral, vascular, glial, or immune influences are absent), we also found that exposure to A␤ caused first a synaptotoxicity (Roselli et al, 2005;Calabrese et al, 2007;Shankar et al, 2007;Evans et al, 2008), which is only later followed by overt neuronal damage. Further strengthening that A␤ causes direct effects on nerve terminals, we showed that A␤ indeed directly impairs synaptosomal function, as observed by others (Mattson et al, 1998;Arias et al, 2002).…”
Section: Discussionsupporting
confidence: 54%
“…In fact, the only morphological change found in the hippocampus of A␤-injected rodents displaying memory deficits was the loss of synaptic markers, whereas neither overt neuronal damage nor astrogliosis nor microgliosis were observed, neither 15 nor 2 d after A␤ 1-42 administration. Accordingly, in cultured neurons (in which peripheral, vascular, glial, or immune influences are absent), we also found that exposure to A␤ caused first a synaptotoxicity (Roselli et al, 2005;Calabrese et al, 2007;Shankar et al, 2007;Evans et al, 2008), which is only later followed by overt neuronal damage. Further strengthening that A␤ causes direct effects on nerve terminals, we showed that A␤ indeed directly impairs synaptosomal function, as observed by others (Mattson et al, 1998;Arias et al, 2002).…”
Section: Discussionsupporting
confidence: 54%
“…In light of several studies describing the neurotoxic effects of synthetic Aβ aggregates or cell-secreted Aβ oligomers (3,(5)(6)(7)(8)(15)(16)(17), we assessed the effects of such preparations on the neuritic cytoskeleton in an attempt to confirm the changes described above with natural dimers isolated from the AD cortex. We examined a synthetic human Aβ40 peptide in which serine 26 is mutated to cysteine (Aβ40 S26C), enabling the formation of stable, disulfidebonded dimers under oxidizing conditions (10,18).…”
Section: Pure Synthetic Aβ Dimers Induce Cytoskeletal Disruption Simimentioning
confidence: 99%
“…Because of the easy maintenance and fast growth rate of these cells, 7PA2 culture medium has provided a convenient tool to investigate the biological activities of low-n Aβ oligomers. This led to the discovery that Aβ oligomers can inhibit hippocampal long-term potentiation (an electrophysiological measure of synaptic plasticity) (67,68), impair complex learned behavior in the live rat (69), and reduce the density of dendritic spines in cultured hippocampal neurons (70,71).…”
Section: Identification Of Neurotoxic Nonfibrillar Aβ Aggregatesmentioning
confidence: 99%